BEHAVIORISME DALAM PEMEROLEHAN KOSAKATA PADA ANAK 3-4 TAHUN MELALUI PERMAINAN NYANYIAN TRADISIONAL - Dona Permana; Agus Syahrani; Mellisa Jupitasari (Universitas Tanjungpura, 2022)
This study aims to describe the types of vocabulary that appear in the language ofchildren aged 3-4 years through traditional games and songs at Sekadau Hulu, and in termsof psycholinguistic behaviorism. This study uses the theory of Psycholinguistic Behaviorism.The research method used is descriptive with a qualitative form. The data source of thisresearch is the speech of children aged 3-4 years which is obtained from traditional gamesand songs. Data collection techniques used in this study were observation, interview,conversational engagement, peer and note-taking techniques. The results of this studyconclude that aspects of linguistic behavior that can be observed directly and therelationship between stimuli (stimulus) and reactions (responses). There are four types ofvocabulary that emerge through the traditional games and songs of Sekadau Hulu Malayuin children aged 3-4 years, namely noun vocabulary, working vocabulary, charactervocabulary, and number vocabulary. There are four types of vacabulary that childrenacquire through traditional games, namely 13 object vocabularies, nine workingvocabularies, two number vocabularies, and two natural vocabularies. While the vocabularyacquired by children through traditional singing consists of four types of vocabulary, namely33 nouns, 11 working vocabulary, one numeric vocabulary, and four character vocabularies.Keywords: Behaviorism, Children aged 3-4 years, Traditional song-games, VocabularyAcquistion.